Biomarkers for REM sleep behavior disorder in idiopathic and narcoleptic patients. Issue 9 (6th August 2019) - Antelmi, Elena; Pizza, Fabio; Donadio, Vincenzo; Filardi, Marco; Sosero, Yuri L.; Incensi, Alex; Vandi, Stefano; Moresco, Monica; Ferri, Raffaele; Marelli, Sara; Ferini‐Strambi, Luigi; Liguori, Rocco; et al.
Abstract: To search for discriminating biomarkers, 30 patients with idiopathic rapid‐eye‐movements sleep behavior disorder (iRBD) were compared with 17 patients with RBD within narcolepsy type 1. Both groups underwent extensive examinations, including skin biopsy searching for phosphorylated α ‐synuclein deposits and whole‐night video‐polysomnography. Skin biopsy was positive for phosphorylated α ‐synuclein deposits in 86.7% of iRBD patients and in none of narcoleptic patients. The analysis of video‐polysomnographic motor events showed differences in their occurrence throughout the night in the two groups. iRBD and RBD due to narcolepsy do have different clinical and pathological findings, confirming a different pathophysiology.